Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

V (x) = x(9-2x) (11-2x)

Sagot :

The expanded form of V(x) = x(9-2x) (11-2x) is V(x)  = 4x^3 - 20x^2 + 99x

How to expand the expression?

The missing information in the question is to express V(x) in standard form

We have:

V(x) = x(9-2x) (11-2x)

Open the brackets

V (x) = x(99 - 2x - 18x + 4x^2)

Evaluate the like terms

V (x) = x(99 - 20x + 4x^2)

Expand

V (x) = 99x - 20x^2 + 4x^3

Rewrite as:

V(x)  = 4x^3 - 20x^2 + 99x

Hence, the expanded form of V(x) = x(9-2x) (11-2x) is V(x)  = 4x^3 - 20x^2 + 99x

Read more about expressions at:

https://brainly.com/question/723406

#SPJ1